Karakteristik Penipuan Sebagai Kejahatan Siber Tertinggi Di Indonesia - Hartanto, Hartanto (Universitas Pancasakti Tegal, 2022)
The development of science and technology will make it easier for people to carry out various activities, and on the other hand this is also used by criminals. Fraud is a crime that has existed since time immemorial (conventional) which is regulated in the Criminal Code, but along with the times, fraudsters also facilitate and improve actions using electronic technology (online) which has been regulated in Law Number 19 of 2016 concerning Information and Transactions. Research describes that crimes that are actually conventional, but when using electronic devices will turn into complex crimes, specifically their spreadability and speed, this is then regulated in a special criminal realm, namely the law on ITE. The method used is normative juridical and the results of the study show that the development of crime is inseparable from the behavior factors of the victim and the environment, then requires adequate countermeasures from law enforcement, namely the Police as a state tool to protect citizens. Examples of fraud cases were added to complement this study.